Influencia de nanopartículas de potasio en el rendimiento y compuestos bioactivos de frutos de melón - Galvan Cardona, Zoraida M.; Preciado Rangel, Pablo; Guillén Enríquez, Reyna R.; Espinosa Palomeque, Bernardo; Sariñana Navarrete, María de los Ángeles; Buendía García, Alain (Ecosistemas y Recursos Agropecuarios, 2025)
Potassium is known as a quality element due to its key role in sugar transport, metabolite biosynthesis, and enzyme activation. This study aimed to determine the optimal dose of potassium nanoparticles (K NPs) in melon plants and evaluate their impact on yield, nutraceutical quality, and K content in the fruits. A field experiment was conducted with melon cv Cruiser, applying four foliar doses of K NPs (100, 200, 300, and 400 mg L⁻¹) and a control treatment (distilled water). The results indicated that foliar application of K NPs significantly affected the nutraceutical quality and K content in melon fruits without impacting crop yield. Melon fruits from plants treated with the intermediate dose (200 mg L⁻¹) showed the highest levels of total soluble solids and firmness. The low dose (100 mg L⁻¹) increased the biosynthesis of flavonoids, total phenols, and antioxidant capacity, while higher doses (300 and 400 mg L⁻¹) reduced bioactive compounds, although they increased the potassium content in the fruits. Foliar application of K NPs is a viable strategy that, when integrated with agronomic practices, can improve the nutraceutical quality of melons without compromising crop yield. However, it is essential to determine the appropriate doses, as low and intermediate doses enhance the fruit’s biophysical and nutraceutical quality, while higher doses may have adverse effects on bioactive compounds.